Se « protéger » derrière son nez rouge ? Le travail émotionnel des artistes-clowns à l’hôpital - Claire Bodelet (Perspectives Interdisciplinaires sur le Travail et la Santé)
This article focuses on an obvious but invisible part of hospital clowns’ work, that of managing their emotions. This specific work enables them to remain creative throughout the day, whatever the wards and situations they have to work in. The hospital is not a "natural" place for clowns to perform, and they must confront a series of situations that can be destabilizing to various degrees. How do clowns manage to do their job in the hospital? How do they work with their emotions? What strategies do they use to deal with difficult emotions and "keep going" in their profession? Based on an interactionist perspective, this analysis: 1) examines the emotional labour that clowns conduct in their daily work in hospitals; and 2) shows how their work organization can be mobilized to regulate emotions. By taking a close look at the specificities of the clowns’ practices, this paper opens up new paths to analyze the multiple ways emotions can serve each performance.